Dental caries experience among school children of Eastern Nepal - significant caries index (Health Renaissance, 2015)
Background: Dental caries, an infectious microbiologic disease of dental hard tissues, is a common public health problem worldwide. The distribution of dental caries studied in any population, shows that a few in the population experience a lot of decayed teeth and most do not experience any at all or experience very little.Objective: To assess the extent and severity of dental caries among 5-12 years old children of eastern Nepal using DMFT(Decayed, Missing and Filled teeth) and SiC (Significant Caries) index.Methods: Six hundred and sixteen 5-12 years old school children were examined for decayed, missing and filled teeth using WHO criteria. DMFT, dft (decayed filled teeth) and SiC Indices were calculated. Results: The mean dft and SiC* were 1.84 and 4.60 respectively, whereas mean DMFT and SiC were 0.33 and 0.92 respectively.Conclusion: SiC gives a better picture of the at risk population, hence it should be widely used along with dft/DMFT.Health Renaissance 2014;12(2): pp 74-77